Study the role of degenerative protein modifications in aging - Guo, Xue (Nanyang Technological University, 2020)
Aging remains one of the biggest unsolved problems in modern society. Oxidative stress derived from overwhelmed ROS plays a pathological role in the aging process of all organs especially brain and skin. Protein damages by degenerative protein modifications (DPMs) which refer to spontaneous nonenzymatic post translational modifications (PTMs) such as oxidation and deamidation have long been regarded as mediators of various human degenerative diseases and natural aging. Brain requires exceptionally high energy consumption and thus is extremely vulnerable to energy metabolism protein damage by unexpected accumulation of oxidative DPMs. The affected enzymes can change the metabolic pathway and bioenergy production in the brain and contribute to mental and cognitive decline in the elderly. Skin is another involved tissue worthwhile for discussion because it has highest ROS load among all organs due to the ROS originating from both external and internal sources. Skin proteins are prone to be oxidative modified and the target protein impaired by oxidative stress may result in the reduced barrier function. In order to understand the roles of DPMs in aging brain and aging skin, in this study we conducted a systematic proteomic study in an aging murine model using label free LC-MS/MS proteomics in discovery phase and quantitative multiple reaction monitoring (MRM) LC-MS/MS in validation phase. In brain sample, TCA component enzymes and their key subunits including SULA2, IDH1, IDH2, SDHB, MDH1, FH1 and NDUFS3 were significantly dysregulated in old murine brain compared with younger mice. The deregulation of these enzymes reveals the imbalance of TCA associated energy metabolism. Moreover, the oxidoreductases, thioredoxin (Trx) and glutaredoxin (Grx) that regulate redox signaling by reversing the sulfenic acid (Cys-SOH) and sulfinic acid (Cys-SO2H) to thiol (Cys-SH) in cysteine were found to be significantly downregulated in old mice brain. The disturbed redox regulation can contribute to oxidative damage in brain proteins by terminal sulfonic acid (Cys-SO3H). Indeed, in-depth mining the discovery proteomic data identified excessive accumulation of cysteine thiol trioxidation in the key catalytic enzymes MDH1 at Cys137 in the old mice group. The accumulation of the oxidative damaged Cys137 in MDH1 was confirmed and measured by MRM method. Trioxidation of cysteine residue will generate sulfonic acid R-S(=O)2-OH. Sulfonic acid is a strong acid and accumulation of sulfonic acid will destroy the cell homeostasis and interrupt the optimal pH for enzymes The 3D simulation showed damaged sites of the enzymes are located at the active zone or the co-factor binding regions, coupled with the kinetic enzymatic activity, indicating the enzymatic activity can be compromised. Catalase (Cat) as a ypical antioxidant defense enzyme against high ROS burden is found to be heavily trioxidized at Cys425 in late age stages including 18 and 24 months in skin sample. These irreversible modification of Cat may lead to additional terminal trioxidation (Cys-SO3H) of other important proteins. Further evaluation the discovery proteomic data identified exclusively accumulation of cysteine trioxidation in two metabolic enzymes associated with cell junction Ctnnb1 at Cys381 and Des at Cys332 in the 18 and 24 months age mice. The high confidence of accumulation of the oxidative damaged Cys381 in Ctnnb1 and Cys332 in Des were confirmed by MRM method. The novel discovery proteomics coupled targeted MRM technique described here have afforded the detection of low-abundant DPMs proteins in mice tissue mixture.